Bank Efficiency Analysis and Stock Return in Indonesia Stock Exchange (IDX) - Riwi Sumantyo; Wayan Nur Aziz Tanca Tresna (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
This study aimed to analyze the efficiency of the banks which are listed in Indonesia Stock Exchange (IDX) and empirically tests the bank effects on the stock returns of each bank. The sample of this study is all banks which are listed in the IDX during the period of 2009 to 2016. Data Envelopment Analysis (DEA) used to measure the bank efficiency in each Decision making units (DMUs), which are obtained as the maximum ratio to know the efficiency level of stock performance by using DEA methods. From the total of 25 banks analyzed, acquired six banks which were always efficient in the period of 2009 to 2016. Moreover, to know the relation between the bank efficiency and the stock return, the regression testing is done by using fixed effect models. The result shows that the bank efficiency of Indonesian banks does not affect their stock return.